The international encyclopedia of educational evaluation - Walberg, Herbert J. \ Haertel, Geneva D. (Oxford : Pergamon Press, 1990)
Evaluation approaches and strategies. Introduction / H. J. Walberg and G. D. Haertel, 3. -- Conduct of and issues in evaluation studies. Introduction / H. J. Walberg and G. D. Haertel, 85. -- Curriculum evaluation. Introduction / H. J. Walberg and G. D. Haertel, 153. -- Measurement theory. Introduction / H. J. Walberg and G. D. Haertel, 233. -- Measurement applications. Introduction / H. J. Walberg and G. D. Haertel, 351. -- Types of tests and examinations. Introduction / H. J. Walberg and G. D. Haertel, 447. -- Research methodology. Introduction / H. J. Walberg and G. D. Haertel, 541. -- Educational policy and planning. Introduction / H. J. Walberg and G. D. Haertel, 667